Association between Attitudes to Self Management on Adherence in Restriction Fluid and Dietary among Patient Hemodialysis Related to Hypervolemia - Mananawan, Sheilla Paulina; Rosa, Elsye Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between hemodialysis patients' attitudes toward self-management and adherence to fluid restriction and hemodialysis diet related to hypervolemia. This research method is a Literature review. The data used in this study comes from reputable journal articles published nationally and internationally in national and international online journals. The results showed that the risk of hypervolemia was reduced when patients could manage their health by performing self-care, developing a self-management plan, and modifying initial diet and renal fluid instructions to adapt to their lifestyle. In conclusion, there is a relationship between self-management and compliance of hemodialysis patients with fluid and dietary restrictions, especially sodium. Keywords: Compliance, Self Management, Fluid Restriction, and Diet